DAMPAK PENERBITAN PENGHASILAN TIDAK KENA PAJAK (PTKP) 2015 TERHADAP PENERIMAAN PAJAK PENGHASILAN (Studi Pada KPP Pratama Kota Cirebon Periode 2014–2015) - Ahmad Syifaudin (Akademi Akuntansi YKPN Yogyakarta, 2016)
This research investigate the impact of adjustment in non-taxable income towards the acceptance level of income taxes both before and after PMK-122/PMK.010/2015 concerning nominal adjustment in non-taxable income by Ministry of Financial in Indonesia issued. The sample drawn from tax payer of PPh 21, PPh 25/29 on private person and PPh 25/29 on legal entity which listed in KPP Pratama in Cirebon City on period of 2014-2015. Data analysis technique which used in this research are descriptive statistic, normality test and paired sample t-test. The result of this research show that the acceptance level of PPh 21, PPh 25/29 on private person is rising insignificantly and the acceptance level of PPh 25/29 on legal entity is rising significantly during on research periods. This result may conclude that the issued of PMK-122/PMK.010/2015 concerning nominal adjustment in non-taxable income by Ministry of Financial in Indonesia have no impact in decreasing the acceptance level of tax incomes especially in KPP Pratama in Cirebon City on period of 2014-2015. Keywords: adjustment in non-taxable income 2015, PMK-122/PMK.010/2015 concerning nominal adjustment in non-taxable income by Ministry of Financial in Indonesia.